2021
DOI: 10.3390/nu13114125
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fat Taste Preference in Progranulin-Deficient Mice

Abstract: Progranulin deficiency in mice is associated with deregulations of the scavenger receptor signaling of CD36/SCARB3 in immune disease models, and CD36 is a dominant receptor in taste bud cells in the tongue and contributes to the sensation of dietary fats. Progranulin-deficient mice (Grn−/−) are moderately overweight during middle age. We therefore asked if there was a connection between progranulin/CD36 in the tongue and fat taste preferences. By using unbiased behavioral analyses in IntelliCages and Phenomast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 84 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Similarly, a study showed ob / ob mice preferred a high-fat diet (HFD, carbohydrate 20 kcal%; protein 20 kcal%; fat 60 kcal%) when compared with control diet (carbohydrate 70 kcal%; protein 20 kcal%; fat 10 kcal%) [ 41 ]. Another study also demonstrated a preference for high fat intake in progranulin knockout mice (Grn−/−), where a preference for 2% milk over 0.3% milk was observed [ 24 ]. This increased consumption of energy resulted in 10% body weight gain, over a period of 7 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a study showed ob / ob mice preferred a high-fat diet (HFD, carbohydrate 20 kcal%; protein 20 kcal%; fat 60 kcal%) when compared with control diet (carbohydrate 70 kcal%; protein 20 kcal%; fat 10 kcal%) [ 41 ]. Another study also demonstrated a preference for high fat intake in progranulin knockout mice (Grn−/−), where a preference for 2% milk over 0.3% milk was observed [ 24 ]. This increased consumption of energy resulted in 10% body weight gain, over a period of 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…This increased consumption of energy resulted in 10% body weight gain, over a period of 7 days. Interestingly, control mice did not demonstrate preference toward fatter milk, and their body weight did not change [ 24 ]. Preference toward fat could be related to dopamine-related pathways [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies on mammals underlined the role of genetic factors in the sensory perception of fats. Schumann et al [39] showed that a progranulin deficiency leads to a decreased expression of CD36 in the tongue, resulting in a greater preference for greasy tastes and fatty foods. When applied to humans, these data suggest that patients with diseases associated with low progranulin levels (for example, compulsive eating associated with frontotemporal dementia, psychiatric diseases, and comorbid obesity) may have a high preference for fatty tastes.…”
mentioning
confidence: 99%